Simulating oil entrapment in clastic sequences - Wendebourg, Johannes (Computer methods in the geosciences, 1997)
The book introduces procedures for simulating migration and entrapment of oil in three dimensions in sequences of sandstones and shales. A principal purpose is to show how simulation experiments can represent oil migration routes and predict places where oil may be trapped in sandstones and intercalated shales. The book derives the differential equations used to represent three-dimensional motions of porewater and oil in sedimentary sequences, and shows how the equations may be transformed into finite form for numerical solution with computers. There is emphasis on the graphic display of solutions, and results of example theoretical and actual applications are presented. The book is directed to geologists who have backgrounds in mathematics and computing and who are engaged in oil exploration and production.